2022
DOI: 10.1111/inm.13067
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review: Alternatives to self‐harm recommended on mental health self‐help websites

Abstract: Less than half of all young people with mental health difficulties will seek professional treatment. Due to the private nature of self-harm it is estimated that only 1:28 young males and 1:18 young females who self-harm ever present to hospital. Self-help supports improved coping strategies and life changes without reliance on a clinical intervention which could be used to reduce self-harming behaviours. The study objective is to review self-help alternatives to self-harm on mental health websites that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The questionnaire aimed to gather information on which techniques and strategies are used or suggested as self-help for young people who self-harm. It was developed from a scoping review of self-help websites (Fenton & Kingsley, 2022) with peer review from CAMHS clinicians, including those working in crisis and inpatient settings. The present study examined a subset of these responses, asking 'how effective have you found advising the following for reducing self-harm episodes in young people?…”
Section: Et Hod S Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire aimed to gather information on which techniques and strategies are used or suggested as self-help for young people who self-harm. It was developed from a scoping review of self-help websites (Fenton & Kingsley, 2022) with peer review from CAMHS clinicians, including those working in crisis and inpatient settings. The present study examined a subset of these responses, asking 'how effective have you found advising the following for reducing self-harm episodes in young people?…”
Section: Et Hod S Designmentioning
confidence: 99%
“…Self‐help strategies, including self‐help toolkits, can be used alongside these therapies to improve overall efficacy, and are advised by the National Institute of Clinical Excellence (NICE) and the Royal College of Psychiatrists as well as several mental health charities (e.g. Fenton & Kingsley, 2022; NICE, 2022). This research aimed to assess the use of self‐help toolkits in current practice in Child and Adolescent Mental Health Services (CAMHS), and the recommended content of such toolkits.…”
Section: Introductionmentioning
confidence: 99%